PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP KOMPETENSI INSTRUKTUR DI UNIT PELAKSANA TEKNIS LATIHAN KERJA (UPT-LK) WILAYAH 1 PROVINSI RIAU - Anuar, Saiful (Eko dan Bisnis: Riau Economic and Business Review, 2021)
ABSTRACT This research was carried out in The Unit Pelaksana Teknis Latihan Kerja (UPT-LK) Region 1 of Riau Province. Does Education and training have a positive and significant effect on the competence of instructors in The Unit Pelaksana Teknis Latihan Kerja (UPT-LK) Region 1 of Riau Province? The purpose of this research is to determine the effect of education and training on instructor competence in The Unit Pelaksana Teknis Latihan Kerja (UPT-LK) Region 1 of Riau Province. The research methods are descriptive and quantitative. The population in this research are Instructors in the Unit Pelaksana Teknis Latihan Kerja (UPT-LK) Region 1 of Riau Province, which amounted to 42 people, while the total sample is the total population, so the number of samples is 42 people. Based on the Simple Linear Regression equations Y = 12,697 + 0,612X. Seen from the Constants of 12,697 means that if the value of independent variable X (education and training) is 0, so the value of dependent variable Y (competence) value is equal to 12,697. T value > t table (4.982 > 2.021) then Ho is rejected, it means there is a significant influence between education and training on competence. So it can be concluded that education and training affect the competence. It can be obtained the number of R Square (R2) of 0.383 or 38.3%. This shows that the percentage contribution, influence of the independent variable (education and training) to the dependent variable (competence) is 38.3%. While the remaining 61.7% is influenced by other variables that are not included in this research.